Peran Pengendali Dalam Melindungi Kepentingan Investor Melalui Pelaksanaan Prinsip Tata Kelola Perusahaan Yang Baik - Setiawan, Muhammad Vikri; Abubakar, Lastuti; Rahmawati, Ema (JURNAL USM LAW REVIEW, 2023)
The aim of this study is to find out and analyze the role of controllers in protecting the interests of publicly-listed company investors by ensuring the implementation of good corporate governance principles. The delay of the implementation of the Annual General Meeting of Shareholders and the publication of annual financial statements are two examples of non-fulfillment of the principles of good corporate governance namely transparency and accountability, which resulting temporary suspending trading of its shares by Indonesia Stock Exchange. When the role of the controller as shareholder who has the ability to control the company is ineffective because the shareholding of the company is less than 50%, the undertake of investors protection become an issue. This research was conducted based on a juridical-normative approach with analytical descriptive specifications based on secondary data. The results of this study revealed that the controller has several mechanisms to control the company to reduce losses for shareholders. However, the determination of a controller with less than 50% shareholding of the company’s shares results in the controlling role towards the company become ineffective and potentially detrimental to the interests of investors. The difference between this research and the previous lies in the object of this study which discusses the role of controllers in ensuring the fulfillment of the principles of good corporate governance so that they can provide protection to investors.